(untitled) (Journal of Medicine, 2021)
Background: Bangladesh is an endemic zone for re-emerging dengue viral infection since 2000. For the last few years, dengue viral outbreak occurs in the rainy season mostly in Dhaka city and seldom sporadic case finds beyond the Dhaka city of Bangladesh. But this outbreak expands also outside the Dhaka city of Bangladesh in 2019. Therefore, with scarcity of data regarding this field in the peripheral part of Bangladesh, we have designed this study among dengue infected patients in Jashore, Bangladesh. Objectives: This observational study aims to assess the clinical presentations, laboratory findings especially hematological changes and outcomes of patients with dengue viral infection at Jashore district in dengue outbreak-2019 in Bangladesh. Methodology: This was an observational study, carried out from 25thApril 2019 to 5thSeptember 2019 during dengue outbreak season in Jashore, Bangladesh. Patients were selected from outpatient department and indoor of a local private hospital in Jashore, Bangladesh who had given informed written consent to participate in our study. Result: Total eligible 77 patients were included in this study. Out of which 70 patients (90.9%) were dengue NS1 antigen Positive on Immunochromatography (ICT) and the rest were anti-dengue IgM antibody positive on ICT method. Around 74 (96.1%) patients had fever as the most common feature in dengue infection. Eighty-seven percentages (87%) of patients had history of headache. Other striking complaints were body ache (66.2%), back pain (51.9%), nausea (55.8%), vomiting (31.2%), anorexia (27.3%), arthralgia (29.9%) and retro-orbital pain (26.0%). Sore throat being a common feature in flu-like illness also found in 18.2% cases. Mean total count of whole blood count (WBC) falls on day 5 (5.76 X 109/L) and then gradually increased. Mean platelet count of study patient was normal throughout the course of the disease process. But, in some cases minimum platelets was found 21 X 109/L at the time of presentation and on day 5 and day 6 which was dropped down to 17 X 109/L. Mean Haematocrit (%) was more or less in a steady state throughout the acute phage of the disease. But, in some cases throughout the hospital stay minimum haematocrit was less than 30% and initially in some cases maximum haematocrit was more than 50% among some dengue infected patients. Total 67 (87%) subjects with dengue viral infection required hospital admission and mean hospital stay was 4 days with a standard deviation (SD) was ±2 days. Blood transfusion was required in only one patient. Around 95% patient was recovered and only 4 cases were referred to the higher centre further better management. Regarding complications, we had found diarrhoea in 9(11.7%) and bleeding disorder in 14.3% patients. Conclusion: In our study, the most common clinical presentations were fever, headache, body-ache, back pain, and gastrointestinal upset. The mean hematological started dropping down from 4th day and gradually improved after 7th day. Some patients developed diarrhea, bleeding disorders and hepatitis as complications during their disease process. We observed a good clinical outcome evident by without having severity and death toll among our study participants. There was very seldom requirement of blood and blood product transfusion in our study. J MEDICINE JAN 2021; 22 (1) : 33-40